2011
DOI: 10.1007/s13197-011-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some qualitative variations in frozen fillets of beluga (Huso huso) fed by different carbohydrate to lipid ratios

Abstract: In this study, juvenile beluga (Huso huso) was fed by the diets containing different carbohydrate to lipid ratios for 5 months. At the end of culture period, proximate compositions of the fish carcasses (moisture, protein, lipid, and ash) were measured. Then, qualitative changes in the fishes were evaluated during 6 months frozen storage (-20 °C) along with recording changes in their Total Volatile Bases Nitrogen (TVN), Thiobarbituric Acid (TBA), Free Fatty Acids (FFA), pH, and muscle texture profile analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Our results showed that there was no regular trend in TBA levels in different treatments during preservation. This is in agreement with the results of frozen storage of beluga fillets (Asghari et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that there was no regular trend in TBA levels in different treatments during preservation. This is in agreement with the results of frozen storage of beluga fillets (Asghari et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, different dietary carbohydrate to lipid ratios did not show any significant differences. Similar results were obtained in our study on frozen storage (Asghari et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The excessive release of ROS in cells induces toxic effects named as oxidative stress, and then produces a large amount of malondialdehyde (MDA), one of most important lipid-oxidation products, which is an important indicator, reflecting peroxidative tissue injury (Janero, 1990;Sharma, Jha, Dubey, & Pessarakli, 2012). Evidence from previous studies suggested that some autolytic enzymes and microbiological effects within muscle could cause muscles to be less elastic and softer, following by a negative impact on fish quality and consumer acceptance (Asghari, Shabanpour, & Pakravan, 2014;Ashton, Michie, & Johnston, 2010). supplementation could elevate antioxidant capacity of fish such as Nile tilapia (Gobi et al, 2018), Clarias gariepinus (Reda et al, 2018) and Product quality is one of the most important factors affecting consumers' purchase of fish food (Gatlin III et al (2007) et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fish muscle texture is based on many intrinsic biological factors such as collagen or fat content. Some autolytic enzymes and microbiological effects could be induced to degradation, which made muscles less elastic and softer (Asghari et al 2014, Xu et al 2015. Casas et al (2006) reported cohesiveness as a parameter to measure muscle elasticity since it describes the ability of the muscle to recover from deformation and its resistance to subsequent deformation.…”
Section: Discussionmentioning
confidence: 99%